SITUS, BUDAYA, DAN STRATEGI PENGEMBANGAN PENELITIAN NEOLITIK DI SULAWESI SELATAN - Nani Somba (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
The most difficult problem in neolitic period analysis is the loss of archaeological context, material resistance, field function transformation and sites damage. Therefore, a strategy is significant to support the research application, such as: priority scale, quality and quantity, finds inventory and detailed location, and lab material analysis availability.